Ultra-Wide Band Antennas for Sixth Generation Systems: Design and Applications - Dwivedi S. (My University, 2025)
The demand for wireless broadband communication is rapidly increasing due to the need to support more users and provide more information about more data. Ultra-wideband (UWB) technology has been developed to cover a very wide bandwidth at many frequencies using very narrow pulses in the nanosecond range and can solve this problem. UWB, a wireless technology designed to transmit information at high speeds over short distances with very low power, is an area of current interest with many applications. This chapter introduces the current UWB technology and its potential applications. It also discusses how these systems can be used without interfering with other existing communication systems. The advantages and disadvantages of these systems have also been examined in detail. Also, the main component which is the most important part of ultra-wide technology is an antenna, has been discussed here. The basic antenna design that can be used for sixth-generation system to enhance the data rates and speed has been mentioned. © 2025 by IGI Global Scientific Publishing. All rights reserved.